Analysis of Outer-Hook Takedown Techniques at The Central Java Provincial Youth Wrestling Championships 2024 - Arif Aprindo; Anggit Wicaksono (Indonesian Journal for Physical Education and Sport, 2025)
The background of this study is that adolescent wrestlers are in the transition period from early category wrestling to the push match style. The research objective was to analyze the success rate of the outside hook takedown technique at the 2024 Central Java Youth Wrestling Provincial Championship. The research method uses a mixed method research design. Data collection uses video recording analysis taken at the match event. The results showed that: 1. The appearance of the takedown technique in the match event amounted to 67 appearances, 2. The successful takedown technique appeared 44 times with a percentage of 66% and for the failed takedown technique appeared 23 times with a percentage of 34%, the average value of the successful takedown technique was 39.90 and the average value of the failed takedown technique was 30.82 then the difference was 9.08, 3. The average value of the successful takedown technique stages: Facing: 9.65, Stepping foot: 10.31, Hand catch: 10.06, and Finishing: 9.86 and failed takedown techniques: Facing: 8.82 Legs: 9.13 Hand catch: 7.47 and Finishing: 5.39 then the difference: Facing: 0.83 Footsteps: 1.18 Hand catch: 2.58 and Finishing: 4,47. The percentage of successful takedown techniques is higher than failed takedown techniques. The research contributes to making it easier for Central Java wrestling coaches to create training programs for youth category wrestlers.